Evaluation of the Incidence of Rotavirus Infection and the Effectiveness of Vaccination in the Khanty-Mansi Autonomous Ugra District in 2014–2018 - A. A. Girina; F. I. Petrovskiy; N. V. Sosykina; A. L. Zaplatnikov (Эпидемиология и вакцинопрофилактика)
Relevance. Rotavirus infection (RVI) is recognized as the main cause of severe gastroenteritis in children worldwide and leads to 527 000 deaths annually.Aim. Present study was intended to evaluate the effectiveness of anti-epidemic measures and vaccination against RVI in children in Pyt-Yakh, Khanty-Mansiysk Autonomous Okrug-Ugra in 2016–2017.Materials and methods. An analysis of the incidence of intestinal infection and RVI was carried out within 2 years prior (2014–2015) to and 2 years after (2016–2017) the implementation of anti-epidemic measures.A separate study was conducted to evaluate the safety and efficacy of a live oral pentavalent vaccine in 593 children including 433 who received three doses of the vaccine in 2016–2017.Results. It was shown that anti-epidemic measures including vaccination decreased the chances of RVI in children aged 0–17 years 1.68 fold in 2017–2018 compared to 2015–2016 (odds ratio (OR) 0.59, 95% confidence interval (CI) 0.49–0.71, p < 0.001). The same data were obtained for children 12 months and younger (OR 0.57, 95% CI 0.35–0.95, р = 0.037) and children aged 1–2 years old (OR 0.62, 95% CI 0.45–0.84, р = 0.002). There were no cases of moderate or severe intestinal infections or hospitalizations in vaccinated population as well as postvaccinal complications.Conclusion. The incidence of intestinal and rotavirus infections in all population in 2018 compared to 2016decreased by 53% and 72% respectively.